Prospek dan Tantangan Penerapan Hybrid Approach dalam Perdagangan Emisi dan Pajak Karbon di Indonesia - Prihapsari, Salsa Juanita; Chairunisa, Hana Kamila (Indonesian Center for Environmental Law, 2023)
A market-based approach as a climate policy instrument to achieve Nationally Determined Contribution (NDC) targets is introduced through an instrument called Carbon Pricing or the Economic Value of Carbon (NEK). NEK aims to internalize the cost of externalities and impose the cost of climate change damage on polluters. Two NEK instruments include emissions trading and carbon tax. Emissions trading puts a cap on emissions that can be released into the atmosphere, while a carbon tax directly sets tax rates on greenhouse gas emissions. However, there are challenges and problems in implementing both. In addition, some countries with similar instruments have different implementation practices. This article finds that a mixed approach can be used if emissions trading and carbon tax are implemented simultaneously. The combination of the two must be well-aligned symmetrically and/or synchronously to achieve NDC targets.